Effect of a selective GABAB receptor agonist, baclofen, on the opioid-induced antinociception and rewarding effect - Arief Nurrochmad; Ozaki Masahiko; Yoshinori Yajima; Minoru Narita; Tsutomu Suzuki (Indonesian Journal of Pharmacy, 2005)
The management of excessive adverse effects is a major clinical problem. Multiple approaches have been described to address this problem. Successful pain management with opioids required the adequate analgesia without excessive side effects. The present study was designed to investigatethe effect of a selective GABAB receptor agonist baclofen on the opioid induced antinociception and rewarding effect. In the present study, we confirmed that either morphine or fentanyl produced a dose dependent antinociceptive effect in mice using tail-flick test. The results demonstratedthat co-administration of baclofen with morphine, fentanyl or oxycodone produced the synergistic effect on antinociception in mice. In the place preference study, we found that baclofen inhibited on morphine or fentanylinduced place preference in rats. These results suggest that coadministrationof baclofen with opioids produce synergistic antinociception with less effects of place preference We propose here that co-administration of baclofen with opioids may pave the way for the new strategy for the control of pain and recommended for the adjuvant drug.Key words : opioid, place preference, rewarding effects, baclofen